Effect of rMnSOD on Survival Signaling in Pediatric High Risk T‐Cell Acute Lymphoblastic Leukaemia. Issue 5 (May 2015) - Pica, A.; Di Santi, A.; D'angelo, V.; Iannotta, A.; Ramaglia, M.; Di Martino, M.; Pollio, M.L.; Schiattarella, A.; Borrelli, A.; Mancini, A.; Indolfi, P.; Casale, F.
<x xml:space="preserve">Abstract</x> Manganese superoxide dismutase (MnSOD) is a mitochondrial enzyme that defends against oxidative damage due to reactive oxygen species (ROS). A new isoform of MnSOD with cytotoxic activity was recently discovered in liposarcoma cells. Here, we tested the effectiveness of a recombinant form of this isoform (rMnSOD) on leukemic T cells, Jurkat cells, and lymphocytes. Our results confirm that leukemic T cells can internalize rMnSOD and that rMnSOD causes apoptosis of 99% of leukemic cells without showing toxic effects on healthy cells. Using light and electron microscopy, we determined that an rMnSOD concentration of 0.067 μM most effective on apoptosis induction. Western blot analysis showed that treatment with 0.067 μM rMnSOD resulted in high expression of the pro‐apoptotic protein Bax and low expression of the anti‐apoptotic protein Bcl‐2 in leukemia cells. Concerning signal transduction pathway no influence was observed after treatment except for Jurkat cells showing a slightly decreased expression of ERK phosphorylation. These results suggest that rMnSOD may be an effective and non‐toxic treatment option for T‐cell leukemia. J. Cell. Physiol. 230: 1086–1093, 2015. © 2014 Wiley Periodicals, Inc., A Wiley Company